Beyond Conventional Care: The use of Alternative Medicine by Head and Neck Cancer Patients in Pakistan – A Retrospective study - Soubia Akhtar; Shayan Khalid Ghaloo; Hamdan Ahmed Pasha; Muhammad Wasif; Rahim Dhanani (Journal of the Pakistan Medical Association, 2026)
Objective: To investigate the prevalence, utilisation and association of diagnostic delay, tumour stage and recurrence with alternative medicine among head and neck cancer patients having undergone surgical resection. Method: The retrospective, cross-sectional study was conducted from March to June 2024 at the Department of Otolaryngology and Head and Neck Surgery, Aga Khan University Hospital, Karachi, and comprised adult patients who underwent surgical resection of primary head and neck cancers from January 1, 2017, to January 31, 2019. Data was collected from the patient electronic medical records related to tumour characteristics along with details regarding treatment and exposure to alternative therapy. Data was analysed using SPSS 23. Results: Of the 125 patients with mean age 46.71±12.6 years, 98(78.4%) were male and 27(21.6%) were female. Overall, 33(26.4%) patients reported AM exposure. Most patients presented with advanced-stage disease 98(83.4%), and 28(28.6%) of them had sought alternative treatments prior to conventional medical care. Majority of patients had an undergraduate education 92(86.6%), were minimum wage earners 114(91.2%), and an early recurrence was noted in 59(47%) cases. There was no significant difference with respect to cancer stage, levels of education and income, and recurrence rate between those who sought alternative medicine and thoe who did not (p>0.05). Conclusion: A significant number of oral cancer patients had utilised alternative medicine. However, the practice was not correlated with disease severity, socioeconomic status or disease recurrence. Key Words: Complementary therapy, Traditional healers, Delayed diagnosis, Recurrence, Herbal medicine.